The Use 3 of Banana Peel Meal (Musa paradisiaca) as Substitution of Corn in the Diets on Performance and Carcass Production of Hybrid Ducks - Bagus Andika Fitroh; Wihandoyo Wihandoyo; Supadmo Supadmo (Buletin Peternakan, 2018)
This study was aimed to evaluate the utilization of banana peel meal as alternatives to substitution of corn in the diets based on the performance, carcass production, intestinal villi, the best type and utilization level of banana peel meal as corn substitution. A total of 105 male day old duck used in a completely randomized design (CRD), i.e. half of it (25%) and all of it (50%) replacing corn with banana peel meal PB= basal feed without banana peel meal; K25 and K50 = basal feed with Kepok banana peel meal; T25 dan T50 = basal feed with Tanduk banana peel meal; R25 dan R50 = basal feed with Raja banana pel meal. each treatment was done through 3 replications, with each replication consisted of 5 hybrid ducks. The data with significant differences were analyzed using orthogonal contrast. The paramater collected include performance (feed consumption, body weight gain, final weight, and feed conversion), carcass and abdominal percentage (carcass weight and carcass percentage). The results of the study showed that the utilization of banana peel meal on ducks had lower yields (P<0.05) in body weight gain, body weight, carcass weight, abdominal fat weight, but had higher feed conversion rather than basal feed treatment. It could be concluded that banana peel meal can not be used as substitution of corn in diets, because it can decrease the performance and carcass production of ducks, banana peel meal Kepok and Tanduk with level of 25% gives best performance and carcass weight when used as substitution of corn.